Will imitators follow pioneer consumers in the adoption of solar thermal systems? Empirical evidence for North-West Germany - Julia Sophie Wörsdorfer; Wolfhard Kaus (Max Planck Institute of Economics, 2010)
In Germany, solar thermal systems (STS) have only diffused to a minor extent yet. This paper analyzes, which demand side factors are decisive for the further proliferation of this environmentally benign technology. Making use of a consumer survey in North-West Germany in 2007, we examine the following parameters: positive environmental attitude, knowledge of the applicability of STS to satisfy consumer needs, and the presence of STS among peer consumers. Drawing upon theoretical foundations from innovation economics and evolutionary consumer theory, we posit that these variables play a different role at distinct stages of the product's diffusion process. Among nonowners, concrete plans to purchase a system within the subsequent two years are distinguished from the general interest to invest into this technology within the next five years. Probitmodels are estimated to test our hypotheses. Our results do not indicate a strong take-off of product diffusion within the next years. By generating interest for the product, knowledge and environmental attitude as well as household income are important determinants of prospective adoptions on the part of the potential imitators. However, only the behavior of peers appears to act as a trigger to the diffusion of this technology.
urn:nbn:de:gbv:27-20110628-141546-0
Keywords: D12; O33; Q42; Q55; 330; innovation diffusion; solar thermal systems; consumer motivations; consumer knowledge; Sonnenenergie; Heizungsanlage; Konsumentenverhalten; Umweltbewusstsein; Innovationsdiffusion; Deutschland